The essence of the system of actors ensuring national security - Truba, Roman; Kozin, Serhii; Vykhrystiuk, Anatolii; Melnyk, Vadym; Shkliarenko, Andrii (Edelweiss Applied Science and Technology, 2024)
The article aims to clarify the actual essence of the system of actors ensuring national security of Ukraine. To achieve the goal of the research, a complex of general and specific methods of scientific knowledge is used (dialectical, abstraction, analysis and generalization, documentary analysis, summarization). It is argued that this system is not a set of entities, because the set of elements does not form a system since it is not characterized by the degree of interaction of its components, which leads to the appearance of a qualitatively new integrity – the form of expression of the structure which actually forms the system. Based on the analysis of scientific literature, it is identified that during the post-Soviet period of the development of the doctrine of national security and its provision, the essence of the complex of actors ensuring national security was understood as a set of these entities. In the current development of these doctrines, this complex is interpreted as a system. The modern understanding of national security and its provision indicates that certain foundations (principles of responsibility, patriotism, and national solidarity) impose requirements extending to a wide range of subjects, encompassing both public service agencies and civil society actors. Furthermore, it creates conditions for holistic interaction between different types of subjects, forming a subsystem of the national security system from these entities. The complex of actors ensuring national security of Ukraine appears as a system because it has its key features.